Electrochemical Hydrogenation of N‐Heterocycles and Related Substrates: A Mini‐Review - Esteban Garcia‐Torres; David E. Herbert (Electrochemical Science Advances)
ABSTRACT Catalytic hydrogenation refers to the (often) metal‐mediated addition of dihydrogen (H2) equivalents to unsaturated compounds to form new element‐hydrogen bonds. This conceptually simple reaction is ubiquitous in the production of a vast number of essential chemicals. Despite a growing recognition of the importance of sustainability in manufacturing, the use of fossil‐derived hydrogen gas and precious metal catalysts in hydrogenation remains widespread. Electrochemical variants of these processes are an appealing alternative, especially those that can make use of sustainable Brønsted acids, more abundant electrode materials and renewable electricity. In this mini‐review, we give a selective overview of electrochemical hydrogenation methodologies for N‐heterocycles and some related substrates from the specific perspective of the synthetic chemistry made possible by this increasingly popular approach.